The Use of an FR1 Schedule Operant Approach-Avoidance Paradigm to Measure the Aversiveness of Neuropathic and Inflammatory Pain - Salcido, Celina A.; Argenbright, Cassie M.; Aguirre, Tiffany; Trujillo, Alex D.; Fuchs, Perry N. (Frontiers in Pain Research, 2022)
Pain is a subjective, private, yet universal phenomenon that depends on a unique combination of sensory, affective, and evaluative characteristics. Although preclinical models have been used to understand much of pain physiology, the inability to communicate with animals limits affective and evaluative feedback and has constrained traditional behavioral methods to adequately represent and study the multidimensional pain experience. Therefore, this study sought to characterize the affective component of pain within a novel operant approach-avoidance paradigm (AAP) to determine which type of pain (inflammatory and neuropathic) may be more aversive. To reveal the possible differences in pain aversiveness within the AAP paradigm, animals received bilateral inflammatory and neuropathic pain conditions and were given the choice to a) forgo appetitive reward by not receiving noxious stimulus of either inflammatory or neuropathic conditions or b) receive noxious stimulus in exchange for an appetitive reward. Although all pain conditions produced significant hypersensitivity, the AAP results revealed there was no preference in the stimulation of a specific paw in the bilateral pain conditions. The finding suggests that despite unique clinical pain characteristics for inflammatory and neuropathic conditions, the lack of observable differences in the pain conditions may not necessarily equate to the overall similarity in aversiveness, but rather that the fixed ratio (FR1) paradigm presentation allowed appetitive reward to be more salient, highlighting the complexities of competing motivational drives of pain and hunger when satiating hunger is always guaranteed. Thus, future studies should seek to further tease apart this relationship with a different schedule and food-controlled methodologies. The development of such preclinical approaches can thoroughly investigate the intricacy of competing drives and likely reveal important information regarding the complexity of pain, enhancing our understanding of pain perception in individuals suffering from comorbid pain states.